Hip Position Acutely Affects Oxygenation and Perfusion of Kidney Grafts as Measured by Functional Magnetic Resonance Imaging Methods—The Bent Knee Study - Mani, Laila-Yasmin; Seif, Maryam; Nikles, Florence; Tshering Vogel, Dechen W.; Diserens, Gaëlle; Martirosian, Petros; Burnier, Michel; Vogt, Bruno; Vermathen, Peter (Frontiers in Medicine, 2021)
Background. Kidney perfusion and oxygenation are two important determinants of kidney graft function. In kidney transplantation, repeated graft hypoperfusion may occur during hip flexion, for example in the sitting position, due to the progressive development of fibrotic tissue around iliac arteries. The aim of this study was to assess the changes in oxygenation and perfusion of kidney grafts during hip flexion and extension using a new functional magnetic resonance imaging (fMRI) protocol. Methods. Nineteen kidney graft recipients prospectively underwent MRI on a 3T scanner including diffusion-weighted, blood oxygenation level dependent (BOLD)- and arterial spin labeling-sequences in hip position 0° and >90° before and after intravenous administration of 20 mg furosemide. Results. Unexpectedly, graft perfusion values were significantly higher in flexed compared to neutral hip position. Main diffusion-derived parameters were not affected by hip position. BOLD-derived cortico-medullary R2* ratio was significantly modified during hip flexion suggesting an intrarenal redistribution of the oxygenation in favor of the medulla and to the detriment of the cortex. Furthermore, the increase in medullary oxygenation induced by furosemide was significantly blunted during hip flexion (p<0.001). Conclusion. Hip flexion has an acute impact on perfusion and tissue oxygenation in kidney grafts. Whether these position-dependent changes affect the long-term function and outcome of kidney transplants needs further investigation.